Factors Affecting Personal Tax Compliance With Sanctions as Moderating Variables (Empirical Study at Primary KPP North Bekasi) - Sri Mulyati; Hadri Mulya (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This research was conducted to examine the factors that influence individual taxpayer compliance with sanctions as a moderating variable. This research  was  conducted  at  the  Primary  Tax  Office  in  North  Bekasi.  Data collection techniques were carried out by distributing questionnaires as many as 170 respondents, but 5 respondents did not return the questionnaire and 165 respondents to the data conducted for the study. The  data  in this study  are primary  data  and  the  method used in  this research is quantitative method, using SPSS (Statistical Package for the Social Sciences version 22). The results of this study indicate that knowledge, tax awareness and tax environment have a positive effect on taxpayer compliance while sanctions as a moderating variable, it has no positive effect on taxpayer compliance.